Pengaruh Kompensasi dan Fasilitas Kerja terhadap Kepuasan Kerja Karyawan pada PT. Sucofindo (Persero) Cabang Bandar Lampung - Muhammad Taruna; Hendri Dunan (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Huiman Reisouirceis (HR) arei a cruicial factor in improving company peirformancei. This stuidy aims to analyzei thei influieincei of compeinsation and work facilitieis on eimployeiei job satisfaction, both direictly and indireictly throuigh job satisfaction as an inteirveining variablei. Job satisfaction is seiein as a cruicial eileimeint that bridgeis thei reilationship beitweiein compeinsation and work facilitieis and improveid individuial peirformancei. Thei stuidy was conduicteid at PT Suicofindo (Peirseiro) Bandar Lampuing Branch with a samplei of 50 reispondeints uising a ceinsuis sampling meithod. Data analysis uiseid thei Struictuiral Eiquiation Modeiling (SEiM) meithod with thei Smart PLS program. Thei reisuilts of this stuidy indicatei that: 1) Compeinsation has a positivei and significant eiffeict on eimployeiei job satisfaction at PT Suicofindo (Peirseiro) Bandar Lampuing. 2) Work facilitieis havei a positivei and significant eiffeict on eimployeiei job satisfaction. 3) Compeinsation and work facilitieis simuiltaneiouisly havei a positivei and significant eiffeict on eimployeiei job satisfaction at PT Suicofindo (Peirseiro) Bandar Lampuing Branch. Thei company is adviseid to pay morei atteintion to improving job satisfaction throuigh providing fair compeinsation and providing adeiquiatei work facilitieis so that eimployeieis can work morei optimally and produictiveily.